Protein Mass and Calcium Mass of Broiler Chicken with Added Nucleotides at Different Maintenance Temperatures - I. Rahmawati; L .D. Mahfudz; S. Kismiati (Jurnal Sain Peternakan Indonesia, 2021)
This study aims to examine the effect of adding nucleotides in broiler rations on the protein mass and calcium mass of broiler chicken reared at different temperatures. The material used was 135 broiler chickens aged 15 days with a weight of 462.20 ± 9 grams of unsex Ross strain and nucleotides imported from China produced by CBH Co. Ltd., China. The study used a completely randomized design (CRD) with a 3x3 factorial pattern with 5 replications. The treatment was carried out at the age of 15-35 days. The treatment given was the first factor adding nucleotides (T0 = nucleotides 0 g/kg feed, T1 = nucleotides 0.5 g/kg feed, T2 = nucleotides 1 g/kg feed) and the second factor was temperature (Heat = S1 = 30 – 32?, Comfortable = S2 = 20 – 23?, Natural = S3 = 24 – 34?). Parameters observed were protein content, calcium content, protein mass, and calcium mass of broiler chicken meat. The research data were analyzed using the F test of variance analysis, if there was a real treatment effect, then Duncan's test was continued. The results showed that there was no interaction between the addition of nucleotides with different maintenance temperatures on protein content, calcium content, protein mass, and calcium mass of meat. Nucleotide 0.05 g had a significant effect (P<0.05) on the protein content of the meat, the natural rearing temperature significantly affected the calcium content of the meat and the comfortable temperature had a significant effect on the protein mass of broiler meat. This study concludes that the addition of 0.05 g of nucleotides can meet the needs of nucleotide synthesis in the body of broiler chickens by increasing the protein content of the meat.